Psycho-economic impact of COVID-19 pandemic on otorhinolaryngology practice in India - Duggal, Prahlad; Gupta, Arun; Gupta, Madhu; Thakur, Jagdeep; Singh, Satinder P.; Singh, Harshvardhan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: COVID-19 pandemic has exposed the soft underbelly of healthcare systems across the world wherein resource limited economies seemed to have taken a greater hit. Present questionnaire-based study was done to determine the perceived threats, psychological stress and economic concerns among practicing otolaryngologists in India, facing COVID-19 pandemic. Methods: A cross-sectional, anonymous, self-reported questionnaire-based study was carried out among otolaryngologists in India over 3 week’s period, during the first countrywide lock-down. An online questionnaire was hosted and publicized using social media. A total of 178 participants landed on the page, 73 were excluded at the first question, 105 otolaryngologists, who were allowed to proceed, completed the questionnaire. Results: Out of 105 otolaryngologists, 57 (52.8%) worked in private-sector. Significantly (p=0.001) higher number of private doctors (66.7%) were afraid of escalated cost of running out-patient clinics compared to government doctors (33.3%). Majority (80.8%) were against performing routine surgeries during pandemic with no significant difference between private and government doctors (p=0.765). Increased stress, during this pandemic was perceived by 73.1%. Conclusions: There were clear indications of psychological stress among the practicing otolaryngologists. Main reasons; anxiety about risk of infection for self, staff members and family, economic impact of the increased protective measures needed. It can be safely concluded based on the study that to alleviate fears of otolaryngologists in India; a comprehensive policy intervention is needed urgently, which is all the more important with the threat of a resurgence looming large over the country.